MILD combustion characteristics of a premixed CH4/air jet flame in hot coflow from a bluff-body burner - Liu, Xiangtao; Wang, Guochang; Si, Jicang; Li, Pengfei; Wu, Mengwei; Mi, Jianchun (Applications in energy and combustion science, 2024)
•MILD and traditional combustion are compared in the same bluff body (BB) burner.•Bluff body creates a recirculation zone, enhancing mixing and combustion stability.•BB-MILD ‘flame’ has higher temperature and NO emission than the case without BB.•Low coflow temperature and oxygen level favor low NO emission from MILD combustion. This numerical study is designated to comparatively investigate premixed CH4/air jet flames from bluff-body (BB) and non-BB (NBB) burners in the coflow of hot exhaust gas. Specifically, traditional combustion (TC) from BB burner (BB-TC), MILD combustion (MC) from BB burner (BB-MC), and NBB burner (NBB-MC) under varying coflow temperatures (TC) and oxygen concentrations (YO2, C) are considered. The flow field, combustion reactions, temperature rise, heat release, along with reaction zone, and pollutant emissions are thoroughly investigated. The findings underscore the feasibility of achieving MILD combustion using the BB burner. Remarkably, the small recirculation zone generated by the BB enhances entrainment and mixing, leading to superior combustion stability and reduced CO emission in the BB-MC case compared to the conventional NBB-MC case. Moreover, the BB-MC case exhibits a higher peak temperature, reaction rate, and heat release rate than the NBB-MC case, albeit with slightly higher NO emission. When compared to the BB-TC case, NO emission from both the BB-MC and NBB-MC cases are significantly lower, particularly under relatively low TC and YO2, C conditions.